Mode of sodium ion action on methanogenesis and ATPase of the moderate halophilic methanogenis bacterium Methanohalophilus halophilus - Smigán, P; Rusnák, P; Greksák, M; Zhilina, T N; Zavarzin, G A (FEBS letters, 1992)
Cells of Methanohalophilus halophilus swelled when exposed to hypotonic solutions of NaCl at pH 7.0. The swelling of the cells ceased in the presence of Mg2+. Methane formation by non-growing cells was strongly dependent on the NaCl concentration. Among other monovalent and divalent cations only Li+ and Mg2+ could partly substitute for a specific function of sodium ions. The artificial Na+/H+ antiporter, monensin, exerted a strong inhibitory effect on methane formation from methylamine. The membrane-bound Mg(2+)-stimulated ATPase of these cells was enhanced at low (40 mM) NaCl concentration while higher concentrations of this solute were inhibitory. The results obtained show that sodium ions are a prerequisite for optimal methane formation and ATPase activity in these cells. However, both of these processes required different sodium ion concentrations.
Keywords: Euryarchaeota; Sodium; Adenosine Triphosphatases; Methane; methylaminy; Methylamines; adenosintrifosfatasy; sodík; methan